Geografia e inovação: o Parque Tecnológico de Sorocaba e as alterações na estrutura industrial da região administrativa de Sorocaba - Oliveira, Willian Prestes de (2021)
This thesis aims to understand how much the actions of the State authority in Sorocaba benefited the municipality and the region in the process of productive restructuring in the state of São Paulo, ensuring the attraction of industries, especially sectors of greater technological intensity to settle in the territory. For the development of the research, it is guided by the authors who deepen the entitled The Geography of Innovation also highlighting the discussions on the attraction factors of industrial activity, the constituent elements of innovation systems, Local Productive Arrangements, and regional innovation systems. It directly addresses elements already established in the region, such as transport infrastructure and higher education institutions, and also those recently created by the State authority in the region of Sorocaba, which makes it an area of interest for the development of industrial activity and for the improvement of regional culture of innovation, highlighting the Sorocaba Technological Park created to serve as a space for interaction between universities, research institutions and companies linked to the technology sector. Ultimately, it undertakes a comprehensive survey of data referring to recent economic transformations in the city and in the Administrative Region of Sorocaba through the data from the IBGE and the RAIS/CAGED platform, analyzing the evolution of the productive structure of Sorocaba using the classification of industrial activities by level of technological intensity, based on the parameters established by the OECD and CNAE 2.0, with greater emphasis on the High Technological Intensity, Medium-High Technological Intensity sectors, jointly considering data on the evolution of the numbers of establishments, sectoral participation in the value of State industrial transformation and on labor in the period of 2008 and 2018.